The aesthetic experience: Project on perception and sound and plastic sensitivity - Jaume-Adrover Magdalena; Berbel-Gómez Noemy (SHS Web of Conferences, 2016)
Light and shadow, sounds and silence, movement and stability have been, since the origin of art, basic, elementary features in every work. They are the material that John Cage, Merce Cunninham, Bob Wilson, László Moholy-Nagy, Alexander Calder, and Llorenç Barber work with. All of whom stand out because of their will to expand the perceptive capacity of the beholder. In the subject of Artistic Projects for Early Childhood Education we have taken some of their works as the starting point of each of the educational projects, posed by pupils. Our aim is not to teach art to boys and girls, or to teach them to appreciate or to recognize works by artists, or even to make musical or plastic compositions. Our proposal lays aside all intentionality and only aspires to strengthen in future educators their own perceptive faculty and their audio-visual sensitivity; so that they, in turn, can release the senses of boys and girls towards a creative situation, of aesthetic experience in listening and looking.